A conflict management tool for conservation agencies. Issue 3 (8th February 2016) - Young, Juliette Claire; Thompson, Des B. A.; Moore, Peter; MacGugan, Alastair; Watt, Allan; Redpath, Stephen Mark
Summary: Growing pressure on natural resources is leading to more conservation conflicts. Governments and their statutory agencies devote increasing financial and human resources to this subject, but tend to adopt reactive, ad hoc approaches to management. We combined theory and empirical data about five conservation conflicts in a transdisciplinary collaboration to co‐develop a novel decision‐making tool. This tool uses a systematic stepwise approach with six distinct decision stages: (i) establishing whether there is a conflict or an impact; (ii) understanding the context of the conflict, including the stakeholders affected; (iii) developing shared understanding of the conflict and goals; (iv) building a consensus on how to reach the goals; (v) implementing measures; and (vi) monitoring the outcomes. Policy implications . We argue this new tool has wide applicability and democratic legitimacy and offers an exciting and practical approach to improve the management of conservation conflicts. Abstract : We argue this new tool has wide applicability and democratic legitimacy and offers an exciting and practical approach to improve the management of conservation conflicts.